2007
DOI: 10.2174/092986707780363032
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Viral Capsid Inhibitors in Human Enterovirus Infection and Associated Diseases

Abstract: Enteroviruses are members of picornavirus family which causes diverse and severe diseases in humans and animals. Clinical manifestations of enterovirus infections include fever, hand, foot, and mouth disease, and herpangina. Enteroviruses also cause potentially severe and life-threatening infections such as meningitis, encephalitis, myocarditis, polio-like syndrome, and neonatal sepsis. With the emergence of enterovirus all over the world as the major causative agent of HFMD fatalities in recent years and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…(Li et al 2007; Vaddiraju et al 2010) Miniaturization, however, stands as a major impediment for amperometric techniques, since reduction in the area of the working electrode generally leads to weaker signal intensity that rapidly approaches noise level. To mitigate this challenge, miniaturized amperometric biosensors are constantly advancing the following four research frontiers:

Enhancement of surface area of the working electrodes by increasing nanoporosity using metal etching and decorating techniques,(Erlebacher et al 2001),(You et al 2003) conducting polymers (Singh et al 2009), carbon nanotubes,(Yu et al 2006) and various nanostructured semiconductors.

…”
Section: Introductionmentioning
confidence: 99%
“…(Li et al 2007; Vaddiraju et al 2010) Miniaturization, however, stands as a major impediment for amperometric techniques, since reduction in the area of the working electrode generally leads to weaker signal intensity that rapidly approaches noise level. To mitigate this challenge, miniaturized amperometric biosensors are constantly advancing the following four research frontiers:

Enhancement of surface area of the working electrodes by increasing nanoporosity using metal etching and decorating techniques,(Erlebacher et al 2001),(You et al 2003) conducting polymers (Singh et al 2009), carbon nanotubes,(Yu et al 2006) and various nanostructured semiconductors.

…”
Section: Introductionmentioning
confidence: 99%
“…VP1, VP2 and VP3 each contain 270 amino acid residues and are located in the exterior of the viral particle. VP1 plays critical roles in adsorption and the uncoating process of the virus [29]. Previous studies showed that the VP1 capsid protein can bind three human proteins including ornithine decarboxylase (ODC1), gene trap ankyrin repeat (GTAR) and KIAA0697.…”
Section: Discussionmentioning
confidence: 99%
“…45 If enteroviruses are found to be a major contributor to its development, then renewed efforts at developing an effective polyvalent enterovirus vaccine, 46,47 and antiviral agents such as pleconaril [48][49][50][51] are certain to follow. This will enable the protection against and/or treatment of enterovirus infections during childhood, to prevent, or at least reduce, both the short-term and long-term complications of these viruses.…”
Section: 8smentioning
confidence: 99%